Dynamic modulation of shared sensory and motor cortical rhythms mediates speech and non-speech discrimination performance - Bowers, Andrew L.; Saltuklaroglu, Tim; Harkrider, Ashley; Wilson, Matt; Toner, Mary A. (Frontiers in Psychology, 2014)
Oscillatory models of speech processing have proposed that rhythmic cortical oscillations in sensory and motor regions modulate speech sound processing from the bottom-up via phase reset at low frequencies (3-10Hz) and from the top-down via the disinhibition of alpha/beta rhythms (8-30Hz). To investigate how the proposed rhythms mediate perceptual performance, EEG was recorded while participants passively listened to or actively identified speech and tone-sweeps in a two-force choice in noise discrimination task presented high and low signal-to-noise ratios. EEG data were decomposed using independent component analysis (ICA) and clustered across participants using principle component methods in EEGLAB. Clustering analysis showed left and right hemisphere sensorimotor and posterior temporal lobe components. In posterior temporal clusters, increases in phase reset at low-frequencies were driven by the quality of bottom-up acoustic information for speech and non-speech stimuli, whereas phase reset in sensorimotor clusters was associated with top-down active task demands. A comparison of correct discrimination trials to those identified at chance showed an earlier performance related effect for the left sensorimotor cluster relative to the left-temporal lobe cluster during the syllable discrimination task only. The right sensorimotor cluster was associated with performance related differences for tone-sweep stimuli only. Alpha/beta suppression was associated with active tasks only in sensorimotor and temporal clusters. Findings are consistent with internal model accounts suggesting that early efferent sensorimotor models transmitted along alpha and beta channels reflect a release from inhibition related to active attention to auditory stimuli. Results are discussed in the broader context of dynamic, oscillatory models of cognition proposing that top-down internally generated states interact with bottom-up sensory processing to enhance task performance.